Assessment Of Primary Immunization Coverage Among The Children Aged 12 - 23 Months In Urban Area Of Bhagalpur City (Journal of Pharmaceutical Negative Results, 2023)
Background: Immunization is one of the most cost-effective interventions that prevent needless suffering through sickness, disability and death. The benefits of immunization are not restricted to improvement in health and life expectancy but also have social and economic impact at both community and national levels. Immunization averts an estimated 2 to 3 million deaths every year from diphtheria, tetanus, pertussis (whooping cough) and measles, however an additional 1.5 million deaths could be avoided if global vaccination coverage improves. Objectives: To assess estimation of the primary immunization coverage in children aged between 12- 23 months. To determine the factors influencing the utilization of immunization services. Methodology: Community based cross sectional study. Study population: Total 450 children. Sampling technique: WHO-30 Cluster sampling. Results: 74.2% of the children were fully immunized, 24.9% were partially immunized and 0.9% were non immunized. The coverage of BCG, OPV3, Pentavalent3, and Measles was 98.0%, 92.9%, 92.9% and 75.5% respectively. Factors like education of parents, place of delivery, birth order of the child, place of immunization, socio- economic status and number of antenatal visits were found to influence the utilization of immunization services in children. Reasons for failure of immunization were obstacles followed by lack of information and lack of motivation. Conclusion: The immunization coverage in the urban area of Bhagalpur has improved markedly over the past years. Sustained improvement of the immunization coverage levels can be achieved by concentrating on the factors which are influencing utilization of immunization services.